Research advance in packet loss processing techniques for VoIP - LI Ru-wei; BAO Chang-chun (Tongxin xuebao, 2007)
The main reasons of packet loss were described and the related techniques of packet loss were introduced.Packet loss processing techniques,which include packet loss concealment and packet loss recovery,were used to recover and conceal the packet loss.And the aim of packet loss prevention was to prevent network congestion in order to reduce the packet loss rate.In addition,the current situation and trend about VoIP were given and discussed.